Piano Triptych “Shadows” by F. Schmitt as a Reflection of the French National Tradition - Mykhailova, Olga (Journal of History Culture and Art Research, 2020)
Abstract The author of the article examines the cultural processes in France, which resulted in the interpenetration of related spheres of creative activity. The role of salons has been noted in fruitful artistic ties to appear, particularly, the friendship of F. Schmitt and M. Ravel. Some parallels between their piano opuses “Shadows” and “Gaspard of the Night” have been found; one of the similarities is the use of poetic text in the form of an epigraph preceding the musical text. The author has made an analysis of the triptych “Shadows” by F. Schmitt in regards to the influence of the poetic images of Lautréamont and W. Whitman on the musical expression means chosen by the composer, and how deeply he materializes the poetic idea. The preceding dedication pieces are designated as a guideline in unraveling the composer’s creative intentions. The properties of the piano texture, melody, harmony, form, dynamics, metro rhythm, and technical equipment of the pieces of the cycle have been summarized. The study also reveals the individual features of the author's style of F. Schmitt, at the head of which lies a multifaceted polyphonized texture, where the vertical structures make one feel the movement of the multilayer whole, the horizontal structures are perceived as a part of harmonious development, and the continuity of their dialogue creates the process linearity and constructive integrity.